Kallikrein-kininogen system activation and bradykinin (B2) receptors in indomethacin induced enterocolitis in genetically susceptible Lewis rats. Issue 3 (1st September 1998) - Stadnicki, A; Sartor, R B; Janardham, R; Stadnicka, I; Adam, A A; Blais, C; Colman, R W
Abstract : Background —The plasma kallikrein-kinin (K-K) system is activated in acute and chronic relapsing intestinal inflammation induced in Lewis rats by intramural injection of exogenous bacterial components. Aims —To determine whether this effect is model specific, K-K system activation was investigated in a modified indomethacin induced enterocolitis model, as well as bradykinin 2 (B2) receptor distribution in the normal and acutely inflamed intestine. Methods —Lewis rats injected with daily sublethal doses of indomethacin for two days developed acute (two days) and chronic (14 days) intestinal inflammation. Plasma prekallikrein (amidolytic), high molecular weight kininogen (HK, coagulant) and cleavage of HK (western blot) were assayed to detect K-K activation. Results —Liver and spleen weights were significantly higher, and body weights and haematocrit values were significantly lower in the indomethacin group than in the control group. During both acute and chronic phases, rats displayed K-K system activation manifested by a significant decrease in plasma prekallikrein and HK functional levels, and by HK cleavage. Plasma T kininogen (a major acute phase protein) was significantly elevated. B2 receptors were identified in both normal and inflammatory intestine with more prominent specific immunohistochemical staining in the acutely inflamed tissue. Conclusions —K-K system activation occurs in association with both acute and chronic phases of intestinal injury, regardless of the triggering agent, suggesting that activation of this system is integrally involved in intestinal inflammation in genetically susceptible hosts. Localisation of B2 receptors across intestinal layers provides a structural basis for the kinin function in the intestine.